A Self-Appraisal Checklist for English Language Arts in Ohio's Elementary Schools. - Ohio State Dept. of Education, Columbus. Div. of Elementary and Secondary Education; Ohio State Dept. of Education, Columbus. Div. of Elementary and Secondary Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This self-appraisal checklist is designed to help Ohio teachers and administrators improve elementary school English/language arts programs. The checklist is organized into seven major categories representing essential aspects of an elementary school English/language arts program: (1) philosophy, (2) organization and administration, (3) class management and instruction, (4) staff, (5) curriculum, (6) facilities and equipment, and (7) evaluation. Each of the seven aspects contains a rating scale, and the booklet concludes with a score comparison graph on which to chart a program's weak and strong areas. (HTH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Evaluation; Elementary Education; English Curriculum; English Instruction; Language Arts; Program Evaluation; Program Improvement; Rating Scales; Self Evaluation (Groups); Ohio; Guides, Non-Classroom.; Tests/Questionnaires.